Forensic applications of Y chromosomal properties. (May 2017) - Khan, Khushbukhat; Siddiqi, Muhammad Hassan; Abbas, Maryam; Almas, Maha; Idrees, Muhammad
Highlights: Y chromosome mode of inheritance is uniparental and does not undergo recombination. Uniparental property – used in personal identification and evolutionary studies. Limitations – rapid mutation and few loci are used in profile generation. Combinatory approach i.e. autosomal STR/Y-STR genotyping as possible solution. The experimental outcomes of MPS are proven cost, money and time effective.